Beauty ideals, myths and sexisms: a feminist stylistic analysis of female representations in cosmetic names - Nur Syuhada Mohd Radzi; Mahfuza Musa (Penerbit Universiti Kebangsaan Malaysia, 2017)
Cosmetic names today carry more than just information on products’ functions or ingredients; they carry dreams, fantasy and stereotypical beliefs of femininity. This study intends to investigate gender representation through advertising language from the perspective of Mills’ (1996) Feminist Stylistics. This research explores the naming devices at word and clausal level, stylistic features and rhetorical devices in order to uncover the extent to which prevailing views of gender are either maintained or challenged. It examines how advertisers and copywriters use language to depict women and how language contributes to such depictions. Findings reveal that the noun phrases are dominated by pre modifiers that function as adjectives to describe the cosmetic names. The notion of gender is also represented in various clause types in which women are not encouragingly depicted, while the stylistic features and rhetorical devices used in cosmetic names reveal traits that are stereotypically prescribed to women. Evidences in which the cosmetic names revolve around gender differences and the patriarchal concept of male domination are extensive. This study hopes to contribute in improving advertising practices, as well as to provide awareness in educating buyers to be more critical when decoding advertising language.